A TECH-ENABLED APPROACH TO TEACHING STUDENTS WITH LEARNING DISABILITIES: A DATA ANALYSIS-BASED STUDY - Daware, Suvarna Vishal; Vaidya, Ravindra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The integration of technology into education has offered significant benefits, especially for students with learning disabilities. This study examines the effects of technology-enabled teaching strategies on the learning experiences of students with disabilities and looks at how educators, parents, and special education specialists view these strategies’ efficacy. 200 participants in the study—teachers, parents, and special educators—gave their opinions using a standardized questionnaire. Questions with closed-ended answers were used to gather quantitative data. The results demonstrate the beneficial influence of assistive technology, customized education software, and adaptive tools in enhancing learning outcomes for students with disabilities. Nonetheless, issues with resource allocation, training, and accessibility were also noted. In order to improve learning for students with disabilities, this study attempts to contribute to the creation of more inclusive, technologically enabled educational methods.